Midkine: Utility as a Predictor of Early Diabetic Nephropathy in Children with Type 1 Diabetes Mellitus - Kotb Abbass Metwalley; Hekma Saad Farghaly; Magda Farghali Gabri; Safwat Mohamed Abdel-Aziz; Asmaa Mohamed Ismail; Duaa Mohamed Raafat; Islam Fathy Elnakeeb (Galenos Yayincilik, 2021)
Objective:This study aimed to assess the role of serum midkine (MK) as a biomarker for early detection of diabetic nephropathy in children with type 1 diabetes mellitus (T1DM) before microalbuminuria emerges.Methods:A total of 120 children with T1DM, comprising 60 microalbuminuric patients (Group 1), 60 normoalbuminuric patients (Group 2), and 60 healthy participants as a control group (Group 3) were included. Detailed medical history, clinical examination, and laboratory assessment of high-sensitivity C-reactive protein (hs-CRP), hemoglobin A1c percentage (HbA1c%), lipid profile, urinary albumin to creatinine ratio (ACR), serum MK and estimated glomerular filtration rate based on serum creatinine were performed in all participants.Results:Both Group 1 and Group 2 had significantly higher serum MK compared to controls (p<0.001). Additionally, significantly higher MK concentrations were present in Group 1 compared with Group 2 (p<0.001). Receiver operating characteristic curve analysis revealed that the MK concentration cutoff value of 1512 pg/mL was able to predict microalbuminuria with a sensitivity of 96% and specificity of 92%. Stepwise regression analysis revealed that HbA1c%, hs-CRP, and ACR were independently related to MK levels (p<0.001 for each).Conclusion:The results of this study suggest that serum MK is a useful, novel, practical marker for the evaluation of renal involvement in children with T1DM, especially in normoalbuminuric children.